2012
DOI: 10.1155/2012/120496
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Features of Dengue Infection in a Schoolchildren Cohort from Medellin, Colombia

Abstract: To determine the incidence of dengue infection, we established active surveillance of febrile episodes in a cohort of schoolchildren from three schools in Medellin, Colombia. We followed a cohort of 2,379 schoolchildren in 2010 and followed 1,840 of these children the following year. During the follow-up time, 264 schoolchildren displayed 297 febrile episodes; of these, 23 episodes (7.7%) were caused by acute dengue infection. All four dengue serotypes were found, and all of the cases were mild. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
(51 reference statements)
1
22
0
1
Order By: Relevance
“…Our seroincidence rate was also comparable with the rates found in prospective cohort studies conducted in Central and South America (5.8-11.1%). 29,31,33 The similarity between our 1-year DENV seroincidence rates and other study populations suggests that Patillas and likely, Puerto Rico can also experience higher rates of DENV transmission.…”
Section: Discussionsupporting
confidence: 66%
“…Our seroincidence rate was also comparable with the rates found in prospective cohort studies conducted in Central and South America (5.8-11.1%). 29,31,33 The similarity between our 1-year DENV seroincidence rates and other study populations suggests that Patillas and likely, Puerto Rico can also experience higher rates of DENV transmission.…”
Section: Discussionsupporting
confidence: 66%
“…17 In brief, from May 2010 to December 2011, school-aged children from grade 5 to 11 were enrolled in a prospective longitudinal study conducted in three schools in Medellin, Colombia. During the study period, dengue cases were identified by school absenteeism due to a febrile episode in the previous 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…During this epidemic year and the following post-epidemic period, an active surveillance study of dengue cases in schoolchildren was performed in the Colombian City of Medellin. 17 We used samples from this study to evaluate the performances of commercially available assays in comparison to ELISPOT-MNT used as a reference method. The specific aims of this study were 1) to evaluate the accuracy of the combination of Panbio ® IgM and IgG Capture ELISAs plus RT-PCR and the accuracy of the SD Bioline Duo rapid test (NS1 Ag and IgM/IgG) for the diagnosis of acute dengue infection in pediatric patients with febrile syndrome and 2) to determine the accuracy and agreement of Panbio ® IgM and IgG Capture ELISAs and SD Bioline Duo rapid test to classify dengue infection in pediatric patients as primary or secondary.…”
mentioning
confidence: 99%
“…1 Dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) are life threatening reversible vascular complications of DF and are associated with severe thrombocytopenia, bleeding and increased vascular permeability. 2 The decreasing platelet counts have found to predict the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%